2017
DOI: 10.21010/ajtcam.v14i2.26
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Action of Xinmailong Injection, a Traditional Chinese Medicine in Cardiac Function Improvement

Abstract: Background: As a bioactive composite extracted from American cockroach, Xinmailong injection (XML) is used for the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…NKA activity was determined according to previous study [22, 23]. H9c2 cells were homogenized in buffer A containing 20 mM HEPES, 250 mM sucrose, 2 mM EDTA, 1 mM MgCl2, pH 7.4, and then centrifuged at 20,000 g for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…NKA activity was determined according to previous study [22, 23]. H9c2 cells were homogenized in buffer A containing 20 mM HEPES, 250 mM sucrose, 2 mM EDTA, 1 mM MgCl2, pH 7.4, and then centrifuged at 20,000 g for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Studies provided evidences to support XML as an effective administration to HF patients that XML injection can mitigate epirubicin-induced cardiotoxicity via activating the PI3K/Akt signaling pathway and inhibiting the Erk1/2 and P38 MAPK signaling pathways [51]. XML can also activate T-type calcium channels and inhibit Na+/K + -ATPase to increase intracellular calcium levels when treating HF [52]. Besides, the pharmacological research on XML has being carried out continuously and many components and functions of XML are being explored [12].…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…Therefore, it is concluded that Xinmailong Injection does not promote Ca 2+ influx through Ca 2+ channels. However, a further study [13] by Li Zhengtao et al using Ca 2+ imaging technology in H9C2 cells revealed that Xinmailong Injection can be inhibited by ML218-HCl (a T-type Ca 2+ channels antagonist instead of Ltype Ca 2+ channel). Therefore, it is believed that Xinmailong Injection can increase cellular Ca 2+ influx by activating Ttype Ca 2+ channels.…”
Section: Mechanism Of Xinmailong Injection Enhancing Myocardialmentioning
confidence: 99%
“…Tian Kunlun and Jiang Yu [12] found that Xinmailong Injection can increase SOD activity and NO 2 − /NO 3 − (ratio of nitrite to nitrate) level, correct acidosis, improve circulating blood flow, and increase urine output in rabbits of ischemiareperfusion injury induced by hypovolemic shock. Li Zhengtao et al [13] found in the cell experiment that Xinmailong Injection can significantly reduce the production of ROS in H9C2 cells and increase the expression of antioxidant enzymes such as superoxide dismutase-(SOD-) 1, SOD-2, and heme oxygenase (HO)-1, which indicates that the protective effect of Xinmailong Injection on cardiomyocytes is achieved by anti-lipid peroxidation and inhibition of OS.…”
Section: Protective Mechanism Of Xinmailong Injection On Cardiomentioning
confidence: 99%